Perkembangan Industri Nasional dan Peran Penanaman Modal - Rohaila Yusof (Jurnal Ekonomi dan Pendidikan, 2011)
This paper discuses about the advantages and disadvantages which happen in the national industries as a result of the dominant of foreign investment Indonesia has been losing the momentum of development of its nation industries. From the 1970s until 1980s. Indonesia had the opportunity to take control of industries in the Asian region, especially as China. Malaysia, and Thailand had still not developed their power to build and develop their industries.Without a good infrastructure and a good logistic, qualified human resources, ability to control technology which support dynamic innovational activity and intensive cooperation between universities and business world, Indonesia will be left behind by any industri from any other country. This paper result, foreign investment is important for the development of industries. Indonesia must try to absorb the advantages deriving from foreign investment. Therefore domestic companies in Indonesia will not  only become the medium but also would be able to absorb the new technology associated with foreign investment.